Homocysteine induces glyceraldehyde-3-phosphate dehydrogenase acetylation and apoptosis in the neuroblastoma cell line Neuro2a - M. Fang; A. Jin; Y. Zhao; X. Liu (Brazilian Journal of Medical and Biological Research, 2016)
High plasma levels of homocysteine (Hcy) promote the progression of neurodegenerative diseases. However, the mechanism by which Hcy mediates neurotoxicity has not been elucidated. We observed that upon incubation with Hcy, the viability of a neuroblastoma cell line Neuro2a declined in a dose-dependent manner, and apoptosis was induced within 48 h. The median effective concentration (EC50) of Hcy was approximately 5 mM. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) nuclear translocation and acylation has been implicated in the regulation of apoptosis. We found that nuclear translocation and acetylation of GAPDH increased in the presence of 5 mM Hcy and that higher levels of acetyltransferase p300/CBP were detected in Neuro2a cells. These findings implicate the involvement of GAPDH in the mechanism whereby Hcy induces apoptosis in neurons. This study highlights a potentially important pathway in neurodegenerative disorders, and a novel target pathway for neuroprotective therapy.